A Century of Snatching: Grave Robbing in Kingston, Ontario - Belyea, Scott (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
This paper examines nineteenth-century body snatching in Kingston, Ontario, focusing on the roles of the medical students, the local medical profession, and community reactions. Drawing primarily on newspapers and documents from the Queen’s University Medical Faculty and the Kingston General Hospital, this chronological and thematic analysis explores the socio-medical evolution of the practice. The results invite reconsideration of earlier body snatching narratives in Canada.